Improvement Of Students 'Capability In Faculty Of Science With PALS Method - Nurul Ihsan; Sepriadi Sepriadi (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
The main problem in this activity is not yet the maximum ability of students and alumni of the Department of Sport Education (JPO) related to entrepreneurship on campus and off campus especially recipients of PMW and PKM. The main problem lies in the managerial ability of business, administration, product quality and other matters related to entrepreneurship. As a result of these problems, the PMW and PKM programs did not run as expected. To achieve this goal, programs are arranged in three patterns, namely Training, mentoring and mentoring. The types of training to be provided are hard skills and soft skills training related to entrepreneurship development. To realize this goal, the team will collaborate with competent institutions in improving human resources, namely the Entrepreneurship Team, Padang State University and the Young Entrepreneurship Development Training Team (Indosinergi Utama Group) as well as the Human Resources Development Training Team (Intan Training Center) and the Ministry of Law and Ham of the West Sumatra region. Participants in this activity were students of the Department of Sport Education FIK UNP who received the PKM and PMW programs and other interested students. In addition, this activity involved interested alumni. The number of participants is limited to only 20 people. The target of this activity is expected to produce a minimum of 2 (two) new science and technology-based independent entrepreneurs per year who are ready to do activities in the community. In addition, there are several products that will be registered with Copyright, Trademark and simple patents. The activities carried out by applying the Active Learning Systems (PALS) partipations method were carried out for 3 months. The results obtained from this activity resulted in the form of 2 new business groups engaged in the delivery of products and services. Product sales in the form of online start ups that sell a variety of bags. While new entrepreneurs in the form of massage services. Furthermore, the outputs in this activity are scientific articles in the first year, and 3-4 minute videos uploaded through social media (youtube). Keywords: Students, Entrepreneurship